The effect of welfare payments on work in a middle-income country - María Caridad Araujo; Mariano Bosch Mossi; Rosario Maldonado; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2017)
We study the impact of welfare payments in Ecuador on the probability that women and men work, and on whether they are employed in the formal or informal sectors. Our analysis is based on two distinct identification strategies and two separate sources of data spanning more than 10 years. We find no evidence that welfare discouraged work. However, among women, welfare payments led to reductions in social security contributions (which are mandated for salaried workers) and payment of VAT and income taxes (which are mandated for the self-employed and firm owners), although the magnitude of these effects is small.
Keywords: H55; I38; J22; 330; welfare; work; formality